THE LEGAL PROTECTION WEAKNESSES ON COSTUMERS OF ONLINE SHOP TRANSACTIONS - Ukie Tukinah (Jurnal Pembaharuan Hukum, 2021)
Electronic transactions that are practiced in online transactions create unequal bargaining power between businesses and customers. Business actors often use the weak position of customers to get the maximum benefit from customers. This study uses a normative juridical approach. The research results obtained include the weaknesses of law enforcement, both from the Customer Protection Agency and the Indonesian Customers Foundation, arguing that there are factors that cause customer protection conditions in Indonesia to be so alarming: First, there is still an asymmetrical relationship between producers and customers. Second, customers generally do not meet sufficient bargaining power against business actors. Third, the Government in general tends to side with business actors. Fourth, there is no sense of concern from existing law enforcement institutions, both from the Police, Attorney General's Office, and the Court.